Fluktuasi Kenaikan Aset, Liabilitas dan Ekuitas Perusahaan Selama Pandemi Covid 19 (Studi Kasus Perusahaan Terdaftar di JII 2018-2020) - Abdullah, Mei K. (AKTSAR: Jurnal Akuntansi Syariah, 2021)
The study aims to test differences in fluctuations in assets, liabilities, and equity of JII-listed companies from 2018-2020. This study uses a quantitative descriptive approach and a paired sample t-test using secondary data. The research object is the company that entered the JII in December-May 2018, 2019, and 2020 (20 companies). The results showed that current assets, fixed assets, total assets, short-term liabilities, long-term liabilities, and equity of JII listed companies from 2018-2019 and 2019-2020 fluctuated, but there was no difference in fluctuations between the period before the Covid-19 pandemic (2018-2019) and after the Covid-19 pandemic (2019-2020).